2021
DOI: 10.1016/j.csbj.2021.04.021
|View full text |Cite
|
Sign up to set email alerts
|

DRscDB: A single-cell RNA-seq resource for data mining and data comparison across species

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Furthermore, the expression of PPO8, SCRB3, and SCRB9 in oenocytoids that feature prominently in our analysis herein, are either found in low abundance or were not detected by Raddi et al (Figure 3-figure supplement 6;Raddi et al, 2020). There is also little similarity when our oenocytoid clusters (Clusters 7 and 8) and Drosophila crystal cell populations (Figure 3-figure supplement 5; Cattenoz et al, 2020;Cho et al, 2020;Tattikota et al, 2020) are compared to previously defined "oenocytoid" cells (Raddi et al, 2020), which according to our analysis and others (Hu et al, 2021) more closely resemble granulocyte populations (Figure 3-figure supplement 7).…”
Section: Comparative Analysis To Other Hemocyte Single-cell Studies In Flies and Mosquitoessupporting
confidence: 43%
“…Furthermore, the expression of PPO8, SCRB3, and SCRB9 in oenocytoids that feature prominently in our analysis herein, are either found in low abundance or were not detected by Raddi et al (Figure 3-figure supplement 6;Raddi et al, 2020). There is also little similarity when our oenocytoid clusters (Clusters 7 and 8) and Drosophila crystal cell populations (Figure 3-figure supplement 5; Cattenoz et al, 2020;Cho et al, 2020;Tattikota et al, 2020) are compared to previously defined "oenocytoid" cells (Raddi et al, 2020), which according to our analysis and others (Hu et al, 2021) more closely resemble granulocyte populations (Figure 3-figure supplement 7).…”
Section: Comparative Analysis To Other Hemocyte Single-cell Studies In Flies and Mosquitoessupporting
confidence: 43%
“…Likewise, single-cell sequencing indicates that Gr8a is expressed in the male and female bitter taste bristles, gustatory receptors, oenocytes, and male reproductive system ( Table 2 ). 54 These data further indicate that in addition to its chemosensory functions, Gr8a may also contribute to oenocyte and male reproductive physiology.
Figure 1 Gr8a is a chemosensory receptor with sexually dimorphic expression in abdominal tissues (A–F) Gr8a -Gal4 labels cells in the proboscis (A and B) and prothoracic legs (C and D) of both males (top) and females (bottom), but only labels cells in the abdomen of males (E and F).
…”
Section: Resultsmentioning
confidence: 75%
“… 87 https://www.phylo.org DRscDB Hu et al. 54 https://www.flyrnai.org/tools/single_cell/web/ Other 20 mL Scintillation Vials, Borosilicate glass, with screw cap, Kimble Chase VWR Cat#490007-896 2 mL screw cap vial clear w/wr 12 mm Agilent Crosslab Cat#5182-0715 Screw cap 12 mm, blue, PTFE-lined, solid top Agilent Crosslab Cat#5183-2075 250ul vial insert, glass with polymer feet Agilent Crosslab Cat#5181-1270 …”
Section: Methodsmentioning
confidence: 99%
“…First we review some of the multiple known functions of SARM1 in different cell types. SARM1 is broadly expressed in many different tissues, and within the nervous system it is expressed within glial and immune cells as well as neurons ( Hu et al, 2021 ). Prior to the discovery of SARM1’s best-known role in axonal degeneration, studies in multiple model organisms have identified SARM1 as an upstream regulator of MAP (mitogen activated kinase) Kinase signaling ( Liberati et al, 2004 ; Chuang and Bargmann, 2005 ; Kim et al, 2007 ; Chen et al, 2011 ).…”
Section: Sarm1-regulated Signaling Mediates Diverse Functions Includi...mentioning
confidence: 99%